Metal-free synthesis of sulfonylated amides through radical aryl migration–desulfonylation. Issue 22 (1st June 2016) - Qiu, Jiang-Kai; Hao, Wen-Juan; Kong, Li-Fang; Ping, Wei; Tu, Shu-Jiang; Jiang, Bo
Graphical abstract: Highlights: A metal-free desulfonylation of N -aryl- N -arylsulfonyl-acrylamides is developed. The mechanism involves 5- exo-trig cyclization, desulfonylation, and aryl migration. This method installs C–S and C–C bonds with cleavage of N–S and C–S bonds. Abstract: A metal-free arylsulfonyl radical-triggered desulfonylation of N -aryl- N -arylsulfonyl-acrylamides under mild conditions for the facile synthesis of a series of sulfonylated amides has been described. The radical transformation simultaneously installs C–S and C–C bonds with concomitant cleavage of N–S and C–S bonds through continuous 5- exo-trig cyclization, desulfonylation, and aryl migration sequence.